Ecologia populacional da manjuba-de-Iguape (Anchoviella lepidentostole) (FOWLER, 1911) no Rio Ribeira de Iguape, sudeste do Brasil - Altafin, Julia Pohl (Universidade Estadual Paulista (Unesp), 2022)
Due to its commercial and regional importance on the south coast of the State of São Paulo, the manjuba-de-Iguape (Anchoviella lepidentostole) is a resource that needs special attention, since the decade of the 1990s, the tendency of overexploitation of the species in the region has been reported, a result that is accentuated due to the lack of information about the populations. Ecological studies using otoliths and fish body morphometry have been used for population and behavioral studies of several species of teleost bony fish, allowing a broad understanding of the life cycle. These methodologies have proved to be effective as an alternative to traditional labeling and recapture methods, and as a complementary tool to molecular biology and parasitology studies. In this context, faced with the challenge of helping in the management of this fishing resource, the objective of this work was to know the migration pattern and population structure of the manjuba-de-Iguape (A. lepidentostole) in the Ribeira de Iguape River, through the use of otoliths and of body morphometry. Thus 91 specimens of A. lepidentostole were collected between the years 2019 and 2021, in Iguape and Registro, in the south of the state of São Paulo. Combined microchemistry, otolith morphology and body morphometric analyzes suggest that the manjuba population collected is unique and homogeneous and that they migrate to the Ribeira de Iguape River in order to complete their reproductive cycle, a result supported by the lack of morphological differentiation of the otoliths. and morphometric of the body of the collected specimens. The results also showed two migratory patterns that corroborate studies already carried out with other species of engraulids, evidencing the high plasticity and environmental adaptation to different salinity gradients of these species. In addition, the life cycle was mostly represented in estuarine environments, which highlights the importance of this environment for the species, possibly due to the greater availability of food and less predation. Therefore, for a better integrated and rational management of this fishery resource, as well as for its conservation, it is necessary to preserve connectivity habitats, especially estuaries and mangrove areas in oligo and mesohaline regions, as they have been intensely occupied by these species.

Devido à importância comercial e regional no litoral sul do Estado de São Paulo, a manjuba- de-Iguape (Anchoviella lepidentostole) é um recurso que necessita de atenção, visto que desde a década de 1990 relata-se a tendência de sobreexplotação da espécie na região, resultado que se acentua devido à falta de informações sobre as populações. Estudos ecológicos com a utilização dos otólitos e da morfometria do corpo dos peixes, vem sendo utilizados para estudos populacionais e comportamentais de diversas espécies de peixes ósseos teleósteos, permitindo uma compreensão ampla do ciclo de vida. Estas metodologias têm se revelado eficazes em alternativa aos tradicionais métodos de marcação e recaptura, e como uma ferramenta complementar a biologia molecular e estudos de parasitologia. Neste contexto, diante ao desafio de auxiliar na gestão desse recurso pesqueiro, o objetivo deste trabalho foi conhecer o padrão de migração e estrutura populacional da manjuba-de-Iguape (A. lepidentostole) no Rio Ribeira de Iguape, através do uso dos otólitos e da morfometria do corpo. Com isso, 91 exemplares de A. lepidentostole foram coletados entre os anos de 2019 e 2021, em Iguape e Registro, sul do estado de São Paulo. Análises combinadas de microquímica, morfologia dos otólitos e morfométricas do corpo sugerem que a população de manjuba coletada é única e homogênea e que migram para o Rio Ribeira de Iguape a fim de completar o seu ciclo reprodutivo, resultado suportado pela falta de diferenciação morfológica dos otólitos e morfométrica do corpo dos exemplares coletados. Os resultados mostraram também dois padrões migratórios que corroboram com estudos já realizados com outras espécies de engraulídeos, evidenciando a elevada plasticidade e adaptação ambiental a gradientes de salinidade distintos dessas espécies. Além disso, o ciclo de vida foi representado, em sua maioria, em ambientes estuarinos, isso evidencia a importância deste ambiente para a espécie, possivelmente pela maior disponibilidade de alimentos e menor predação. Portanto, para uma melhor gestão integrada e racional desse recurso pesqueiro, bem como para sua conservação, se faz necessário a preservação dos habitats de conectividade, principalmente os estuários e áreas de manguezais nas regiões oligo e mesohalinas, pois se mostraram intensamente ocupadas por essas espécies.
Population ecology of the manjuba-de-Iguape (Anchoviella lepidentostole) (FOWLER, 1911) in the Ribeira de Iguape River, southeastern Brazil
Keywords: Ecologia; Manjuba (Peixe); Microquimica; Morfologia; Morfometria